2008
DOI: 10.1021/bi702445j
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Kinesin Holoenzymes Are Composed of Heavy and Light Chain Homodimers

Abstract: Conventional kinesin is a major microtubule-based motor protein responsible for anterograde transport of various membrane-bounded organelles (MBO) along axons. Structurally, this molecular motor protein is a tetrameric complex composed of two heavy (kinesin-1) chains and two light chain (KLC) subunits. The products of three kinesin-1 (kinesin-1A, -1B, and -1C, formerly KIF5A, -B, and -C) and two KLC (KLC1, KLC2) genes are expressed in mammalian nervous tissue, but the functional significance of this subunit he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
109
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(112 citation statements)
references
References 50 publications
3
109
0
Order By: Relevance
“…The functional kinesin-1 tetramer is now known to comprise two homodimers, each containing a single KLC isoform (KLC1 or KLC2); heterotetramers containing both KLC1 and KLC2 do not exist in vivo (DeBoer et al, 2008). Transfection of KLC1wt, KLC1ser460ala or KLC1ser460asp greatly increased KLC1 expression (Fig.…”
Section: Mutation Of Klc1ser460 Modulates Binding Of Calsyntenin-1mentioning
confidence: 99%
See 1 more Smart Citation
“…The functional kinesin-1 tetramer is now known to comprise two homodimers, each containing a single KLC isoform (KLC1 or KLC2); heterotetramers containing both KLC1 and KLC2 do not exist in vivo (DeBoer et al, 2008). Transfection of KLC1wt, KLC1ser460ala or KLC1ser460asp greatly increased KLC1 expression (Fig.…”
Section: Mutation Of Klc1ser460 Modulates Binding Of Calsyntenin-1mentioning
confidence: 99%
“…During the course of our study, others also identified KLC1ser460 as a phosphorylation site through mass spectrometry sequencing of the phosphoproteome (Daub et al, 2008;Dephoure et al, 2008), including in mouse brain (see http://www.phosida.com/). KLC1 and calsyntenin-1 are both enriched in neurons (DeBoer et al, 2008;Hintsch et al, 2002), so we additionally analysed phosphorylation of KLC1ser460 in endogenous KLC1 isolated by immunoprecipitation from cultured rat cortical neurons. Again, we identified KLC1ser460 as a phosphorylated residue (Fig.…”
Section: Klc1 Is Phosphorylated On Serine 460mentioning
confidence: 99%
“…By far the best-characterized kinesin involved in lysosome transport is kinesin-1 (Figs 3 and 4). This kinesin is a heterotetramer composed of two heavy chains (KIF5A, KIF5B or KIF5C) and two light chains (KLC1, KLC2, KLC3 or KLC4) (DeBoer et al, 2008). Kinesin-1 is recruited to lysosomes by a chain of interacting proteins, including the multisubunit BLOC-1-related complex (BORC), the Arf-like small GTPase Arl8 (which has two isoforms in mammals, Arl8a and Arl8b, hereafter generically referred to as Arl8), and the Arl8 effector SifA and kinesin-interacting protein (SKIP, also known as PLEKHM2) (Boucrot et al, 2005;Bagshaw et al, 2006;Hofmann and Munro, 2006;Rosa-Ferreira and Munro, 2011;Pu et al, 2015) (Fig.…”
Section: Anterograde Transportmentioning
confidence: 99%
“…In contrast, kinesin-1C knockout mice are viable, although they exhibit loss of some motor neurons and a slight decrease in overall brain size (Kanai et al, 2000). Recent evidence indicates that kinesin-1A, B, and C heavy chains form homodimers (DeBoer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, kinesin-1C knockout mice are viable, although they exhibit loss of some motor neurons and a slight decrease in overall brain size (Kanai et al, 2000). Recent evidence indicates that kinesin-1A, B, and C heavy chains form homodimers (DeBoer et al, 2008).Additional evidence that kinesin-1 is a motor for neurofilaments has come from studies on kinesin-1A knockout mice by Goldstein and colleagues (Xia et al, 2003). The conventional knockouts (type I deletion) died shortly after birth, so the authors created conditional knockouts (type II deletion) by using a Cre-lox strategy.…”
mentioning
confidence: 99%